Tinjauan Fatwa No.108/DSN-MUI/X/2016 Terhadap Strategi Pengembangan Wisata Halal Di Puncak Ratu Pamekasan - Havida, Lailatul Wahyu; Mohamad Ali Hisyam (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
This research aims to find out strategy for developing halal tourism in Puncak Ratu Pamekasan in terms of Fatwa No.108/DSN-MUI/X/2016. With this research, it is hoped that it can develop the potential for halal tourism, especially in Pamekasan. This research uses qualitative methods with a literature study and field study approach, data collection by observation, interviews and documentation. The research results show that the Puncak Ratu tourism development strategy includes five components of tourism development, namely attraction, accessibility, aminities, ancillary services & institution. The Puncak Ratu tourism development strategy towards a halal tourist destination based on the perspective of Fatwa No.108/DSN-MUI/X/2016 concerning Guidelines for Organization Tourism Based on Sharia Principles has been implemented limited to the aspect of the availability of infrastructure in the form of worship facilities, clean water sanitation and canteens that sell halal food. However, several points have not been met, such as non-muhrim visitors holding hands and final waste disposal that has not been managed properly. To become a halal tourist destination, Puncak Ratu needs further efforts to implement the points in Fatwa No.108/DSN-MUI/X/2016, especially in the seventh decree, namely regarding provisions on tourist destinations.